A Case Report of Heart Failure with Atrial Fibrillation and Peripheral Vascular Resistance - Sarella, Prakash Nathaniel Kumar; Gudapati, Harshika; Asogwa, Patrick Oliver; Kakarparthy, Ravishankar (Indian Journal of Pharmacy Practice)
Heart failure in elderly patients often presents with atypical manifestations due to the high prevalence of comorbid conditions. Symptoms may be subtle and under-reported. Timely diagnosis of heart failure and treatment of comorbidities are crucial for effective management. We describe a 75-year-old female with a history of similar complaints who presented with pedal edema, shortness of breath, and fatigue. Investigations revealed atrial fibrillation, severely reduced left ventricular function, and increased forearm vascular resistance suggesting peripheral vascular disease. Laboratory tests showed decreased uridine diphosphate levels. This case highlights the diagnostic challenges of heart failure in elderly patients with multiple comorbidities. Atypical presentations are common and timely recognition of underlying heart failure is needed to optimize management and prevent exacerbations. Treatment of comorbid conditions like atrial fibrillation and peripheral vascular disease may also help improve outcomes.
Keywords: Comorbidity; Differential Diagnosis; Elderly patients; Heart failure; Multiple coronary disease